Proporsi tepung ampas kelapa dan tepung ubi jalar ungu terhadap karakteristik fisik, kimia dan organoleptik pie susu - Gisela Puspa W Anindya; Hiasinta A Purnawijayanti; Veronica Ima Pujiastuti (Nutrition Scientific Journal, 2023)
Fiber requirements according to the 2019 RDA are 37 g/day for men and 32 g/day for women aged 19-29 years. Indonesian people consume an average of 10.5 g of dietary fiber per day, in other words, they only meet about a third of their ideal needs. Low consumption of fiber can cause various degenerative diseases. These problems can be overcome by developing high-fiber foods by utilizing coconut dregs flour and purple sweet potato flour as raw materials for making products such as milk pie. This study aims to determine the effect of the proportions of coconut dregs flour and purple sweet potato flour on the physical, chemical, and organoleptic characteristics of milk pie. This research is an experimental study using a completely randomized design [CRD] with 4 treatments and 3 repetitions. The panelists who were involved in the organoleptic test were 30 students of the Undergraduate Nutrition Study Program, STIKes Rapih Yogyakarta. The results showed that the proportions of coconut pulp flour and purple sweet potato flour affected toward[p-value 0.05] moisture content, dietary fiber content, appearance, aroma, taste, and overall preference , but had no effect [p-value 0.05]. The level of crispiness, and texture of the milk pie. The milk pie product in this study can be categorized as a high-fiber product so that it can be used as an alternative product to increase fiber consumption.